A STUDY OF LEPTIN & LIPID PROFILE IN A SAMPLE OF IRAQI PATIENTS WITH KNEE OSTEOARTHRITIS. - Turki, Kismat M.; Alosami, Mohammed H.; Abdul-Qahar, Zina H. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: New data suggests that joint damage in Knee Osteoarthritis (KOA) may be caused by systemic factors like adipose tissue products; Adipokines, which may provide a metabolic link between obesity & KOA. Recently, one of the known adipokines named LEPTIN has been linked to KOA because it can be detected in serum & synovial fluid of patients with KOA. Objective: To evaluate the contribution of Leptin & serum lipids to the pathophysiology of Osteoarthritis in Iraqi patients with Knee OA. Subjects& Methods: The study was carried on 90 subjects divided into four groups: Knee Osteoarthritis cases group (n=60). Control group (n=30). Obese subjects group (n=60). Non-obese subjects group (n=30). KOA cases were diagnosed clinically whereas obesity was specified by BMI ≥25kg/m2. For all subjects studied measurements of fasting serum leptin and lipid profile have been done. Results: Mean serum leptin level was significantly higher in KOA cases compared to control group (P<0.001), and higher in obese than non-obese subjects (P<0.001). Serum leptin level also showed a strong positive correlation with BMI (r=0.501, P<0.01). Conclusions: Leptin may play an important role in the pathogenesis of KOA. In addition abnormal lipid profile and obesity are important risk factors for KOA.